Docência universitária: o desafio de ensinar na atualidade - Silva, Valéria Alves da (2006)
The objective of the present paper is to make a reflection about the formation of the university teaching staff in undergraduate courses, aiming to notice if the practice of this teaching practice is related to the contemporary world s demands facing the Brazilian Legislation. During the process of investigation the quarti-qualitative approach was used believing that the use of these two types of analyses allows the establishment of more significant conclusions through the data acquired, in this research questionnaire with open and closed questions was opted. The subjects are university teachers that perform in undergraduate courses, in a private Higher Education Institution from Triângulo Mineiro, in the city of Araguari MG. It is believed that the formation of the university teacher is essential, but is observed that this formation in most of the times is poor and compromises the practice of these teachers. Besides this factor, the Brazilian Legislation demands for the teaching practitioner in Higher Education preferably that he has a master or doctor title and we still have the changes that occurred because of the globalization that requires an even better and more prepared professional. This way, it has became necessary that the higher Education institutions provide their teachers a rethinking about their performance and also moments of reflection about the changes occurred in the word and about their pedagogical practice. The results of the research allow us to affirm that a great part of the teachers doesn t have and adequate pedagogical formations that corresponds to the requirements of the world nowadays, this pedagogical needing reflects directly to our routine inside the classroom. It was possible to notice, also, that the teachers are aware of this formation necessity and they search for this quality in master and doctor courses, these courses correspond to the Brazilian Legislation in relation to the title, but they lack a pedagogical concern, the teacher show they are worried about their formation and they recognize the need of a permanent skillness and feel eager to find alternatives to improve their performance in the classroom. The Higher Education Institution researched offers a postgraduation course in Higher Education Methodology, but it can be noticed that is isn t enough. The proposal in the end of this paper, among other suggestions, is that the institution creates a permanent skillness program that can contribute for the improvement of the Higher Education quality.